2022
DOI: 10.3390/jcm11092539
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Recovery and Understanding Long-Term Deficits in Balance, Ankle Mobility and Hip Strength in People after an Open Reduction and Internal Fixation of Bimalleolar Fracture and Their Impact on Functionality: A 12-Month Longitudinal Study

Abstract: To analyze how balance and other physical capacities evolved after surgery in patients with a bimalleolar fracture and how these capacities and clinical variables (immobilization or unloading time) contribute to restoring patients’ functionality, 22 patients and 10 healthy people (HC) were assessed for static and dynamic balance (Y-Balance test, YBT), dorsiflexion ankle mobility (ADFROM) and hip strength at 6 and 12 months after surgery. Patients’ functional status was assessed through the Olerud Molander Ankl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Complementary to these functional scales, clinical parameters such as ankle dorsiflexion range of motion (ADF ROM), level of swelling, and muscle atrophy provide objective measures of clinical status at different stages of rehabilitation [18,26,27]. The recovery of these parameters after ankle surgery is critical and may play an important role in the full recovery of gait functionality [28] or balance [29].…”
Section: Introductionmentioning
confidence: 99%
“…Complementary to these functional scales, clinical parameters such as ankle dorsiflexion range of motion (ADF ROM), level of swelling, and muscle atrophy provide objective measures of clinical status at different stages of rehabilitation [18,26,27]. The recovery of these parameters after ankle surgery is critical and may play an important role in the full recovery of gait functionality [28] or balance [29].…”
Section: Introductionmentioning
confidence: 99%
“…Elam et al [ 11 ] reported that postural sway in healthy older adults increased after two weeks of unilateral above-knee cast immobilization. Following lower limb surgery, patients may experience postural instability due to secondary dysfunction (i.e., muscle weakness and reduced range of motion) [ 12 ]. The reports by Caplan et al [ 10 ] and Elam et al [ 11 ] suggest that movement restriction of the unilateral limb itself is a factor that inhibits postural control.…”
Section: Introductionmentioning
confidence: 99%